Evaluating cell viability, capillary perfusion, and collateral tortuosity in an ex vivo mouse intestine fluidics model - Willi, Caroline E.; Abdelazim, Hanaa; Chappell, John C. (Frontiers in Bioengineering and Biotechnology, 2022)
Numerous disease conditions involve the sudden or progressive loss of blood flow. Perfusion restoration is vital for returning affected organs to full health. While a range of clinical interventions can successfully restore flow to downstream tissues, the microvascular responses after a loss-of-flow event can vary over time and may involve substantial microvessel instability. Increased insight into perfusion-mediated capillary stability and access-to-flow is therefore essential for advancing therapeutic reperfusion strategies and improving patient outcomes. To that end, we developed a tissue-based microvascular fluidics model to better understand (i) microvascular stability and access-to-flow over an acute time course post-ischemia, and (ii) collateral flow in vessels neighboring an occlusion site. We utilized murine intestinal tissue regions by catheterizing a feeder artery and introducing perfusate at physiologically comparable flow-rates. The cannulated vessel as well as a portion of the downstream vessels and associated intestinal tissue were cultured while constant perfusion conditions were maintained. An occlusion was introduced in a selected arterial segment, and changes in perfusion within areas receiving varying degrees of collateral flow were observed over time. To observe the microvascular response to perfusion changes, we incorporated (i) tissues harboring cell-reporter constructs, specifically Ng2-DsRed labeling of intestinal pericytes, and (ii) different types of fluorescent perfusates to quantify capillary access-to-flow at discrete time points. In our model, we found that perfusion tracers could enter capillaries within regions downstream of an occlusion upon the initial introduction of perfusion, but at 24 hours tissue perfusion was severely decreased. However, live/dead cell discrimination revealed that the tissue overall did not experience significant cell death, including that of microvascular pericytes, even after 48 hours. Our findings suggest that altered flow conditions may rapidly initiate cellular responses that reduce capillary access-to-flow, even in the absence of cellular deterioration or hypoxia. Overall, this ex vivo tissue-based microfluidics model may serve as a platform upon which a variety of follow-on studies may be conducted. It will thus enhance our understanding of microvessel stability and access-to-flow during an occlusive event and the role of collateral flow during normal and disrupted perfusion.